Kompetensi Guru dan Implementasinya dalam Pembelajaran - Eny Fatimatuszuhro Pahlawati (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2019)
In the teaching and learning process involves two active actors, namely teachers and students. The teacher as the teacher is the creator of student learning conditions that are designed intentionally, systematically, and continuously. While children as subjects of learning are those who enjoy the learning conditions created by a teacher. But in reality teachers who have good competence are very rarely found, this is due to the existence of several factors that are less supportive including factors of educational background, teaching experience, and mastery of the material. Therefore this scientific work aims to determine Teacher Competence and Its Implementation in Learning. The results of this scientific work show that teacher competency is a combination of personal, scientific, technological, social, and spiritual abilities that balance form teacher professional standard competencies, which include mastery of material, understanding of students, educational learning, personal development, and professionalism.